A responsabilidade civil por atos lesivos decorrentes de inteligência artificial nas relações de consumo em ambiente virtual - Figueiredo, Mario Augusto Carvalho de (2020)
Artificial intelligence is human-like intelligence displayed by mechanisms or software. It is a system that perceives its environment and takes actions that maximize its chances of success. As is known, the technological tool of artificial intelligence or cognitive computing is increasingly used as a way to optimize the intended results. In this same context, we have the figure of the consumer who, often without knowledge, is exposed and establishes different relationships in which this technology tool is used. The objective of this work will be to analyse how civil liability for harmful events caused by artificial intelligence will occur, especially in the virtual environment and considering the vulnerability of the consumer. All of this will be analysed by the specifically consumerist regime disciplined in the CDC and the extent to which the legislation specifically addresses the problem of liability in a virtual environment, in which the Marco Civil da Internet (Law 12.965 / 2014) stands out, with its respective regulation by Decree nº 8.771 / 2016, and the General Data Protection Law (Law nº 13.709 / 2018)